The Economics of Low-Income Diets - Sorenson, Helen L.; Gilboy, Elizabeth W. (Quarterly Journal of Economics, 1937)
New attitudes and new standards, 663. — The data, 664. — Income elasticities for different foods, 665. — Calorie content of diets, 669. — Comparisons with scientifically determined diets, 671. — Nutrition and education, 676. — Nutrition and income, 677. — Nutrition and agricultural poHcy, 679.